Cloud-Based Environmental Monitoring to Streamline Remote Sensing Analysis for Biologists. (29th September 2021) - Stahl, Amanda T; Fremier, Alexander K; Heinse, Laura
Abstract: Timely, policy-relevant monitoring data are essential for evaluating the effectiveness of environmental policies and conservation measures. Satellite and aerial imagery can fill data gaps at low cost but are often underused for ongoing environmental monitoring. Barriers include a lack of expertise or computational resources and the lag time between image acquisition and information delivery. Online image repositories and cloud computing platforms are increasingly used by researchers because they offer near-real-time, centralized access to local-to-global-scale data sets and analytics with minimal in-house computational requirements. We aim to broaden knowledge of these open access resources for biologists whose work routinely informs policy and management. To illustrate potential applications of cloud-based environmental monitoring (CBEM), we developed an adaptable approach to detect changes in natural vegetative cover in an agricultural watershed. The steps we describe can be applied to identify opportunities and caveats for applying CBEM in a wide variety of monitoring programs.